(untitled) (CIPEEX, 2025)
Objective: To conduct a systematic review and meta-analysis to investigate the effects of preoperative duloxetine on short-term outcomes after laparoscopic surgeries. Methods: MEDLINE, Embase, and the Cochrane Library were systematically searched for randomized controlled trials comparing preoperative duloxetine vs. placebo in adults undergoing laparoscopic surgery. Risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were used for dichotomous and continuous outcomes, respectively, using a random-effects model. Statistical significance was considered at p<0.05. Results: Four trials (227 patients) were included. Compared to placebo, duloxetine provided significantly lower pain scores at 2 (MD -1.04; 95% CI -1.75, -0.33), 4 (MD -1.28; 95% CI -1.77, -0.79), 8 (MD -1.22; 95% CI -1.72, -0.72), 12 (MD -1.64; 95% CI -2.88, -0.41), and 24 hours (MD -1.05; 95% CI -1.72, -0.39) after surgery. Duloxetine led to a significantly longer time between the end of surgery and the first request for analgesia by the patient (MD 128.38 minutes; 95% CI 41.31, 215.46), compared to placebo. Furthermore, the group that received duloxetine had a significantly lower risk of nausea/vomiting (RR 0.48; 95% CI 0.25, 0.90), while there were no significant differences between the groups regarding the risk of dizziness, headache, and somnolence. Conclusion: Compared to placebo, the administration of duloxetine before laparoscopic surgeries significantly reduces postoperative pain intensity, delays the need for analgesia, and reduces the risk of nausea/vomiting.